The soul and the future of education - Reljić, Slobodan (Sociološki pregled, 2018)
During the time of the domination of the liberal political ideology, school curricula become instruments of “scientific humanism”. Schools were totally committed to “mundane values”. At the beginning of the third millennium, it is certain that geopolitical turn will occur. This process could summarize in the slogan “The rise of Asia and Fall of America”. It has an impact on the transformation of the values that school system have to establish and continually reproduce. Some theorists, this process of transformation of a set of the values call “return to a soul”. An ongoing process of transformation of the set values is not merely a process with religious meaning. The change of values that comes along with geopolitical turn, is more focused on the new ways of establishing fruitful and subtle connections with the world and other persons. The other person or persons are not seen as an instrument for our own selfinterest or some kind of obstacle towards realisation, protection or advancement of our own egoism. The other person or persons are seen as a soul. The birth of the new set of values is a permanent and complex process with an uncertain outcome burdened with a huge level of historical and social uncertainties This article is trying to sketch who will be the main agents of change of values and how this process will be carried out in the near future.